The Upper Albian ammonite succession in the Montlaux section, Hautes-Alpes, France - Kennedy, W; Latil, J (2007)
A 100 metre succession of Upper Upper Albian sediments in the Montlaux section (les Gipieres-Champfleury), Alpes-de-Haute Provence, France yielded a series of ammonites that provide unequivocal evidence for a Mortoniceras (Subschloenbachia) rostratum ammonite Zone succeeded by a Mortoniceras (Subschloenbachia) perinflatum ammonite Zone. On this basis, and evidence from successions described previously, the classic Upper Upper Albian Stoliczkaia dispar Zone is replaced by a sequence, from oldest to youngest, of Mortoniceras (Mortoniceras) fallax, Mortoniceras (Subschloenbachia) rostratum, Mortoniceras (Subschloenbachia) perinflatum and Arrhaphoceras (Praeschloenbachia) briacensis Zones. The following species are described: Anagaudryceras sacya (FORBES, 1846), Desmoceras latidorsatum (MICHELIN, 1838), Puzosia (Puzosia) mayoriana (D'ORBIGNY, 1841), Pleurohoplites renauxianus (D'ORBiGNY, 1840), Arrhaphoceras sp., Discohoplites simpex WRIGHT and WRIGHT, 1949, Discohoplites sub-falcatus (SEMENOV, 1899), Mortoniceras (Subschloenbachia) rostratum (J.SOWERBY, 1817), Mortoniceras (Subschloenbachia) perinflatum (SPATH, 1922b), Stoliczkaia (Stoficzkaia) dispar (D'ORBIGNY, 1841), Stoliczkaia (Stoliczkaia) clavigera NEUMAYR, 1875, Anisoceras armatum (J.SOWERBY, 1817), Anisoceras per-armatum PICTET and CAMPICHE, 1861, Anisoceras pseudoelegans PICTET and CAMPICHE, 1861, Idiohamites elegantulus SPATH, 1939, Hamites venetzianus PICTET, 1847, Lechites (L.) gaudini (PICTET and CAMPICHE, 1861), Lechites (L.) moreti BREISTROFFER, 1936, Mariella (Mariella) bergeri (BRONGNLART, 1822), Ostlingoceras (Ostlingoceras) puzosianum (D'ORBIGNY, 1842), and Scaphites (Scaphites) sp.